IMPLEMENTASI MANAJEMEN RISIKO PADA LEMBAGA KEUANGAN NON-BANK SYARIAH (STUDI ANALISIS UNIT SIMPAN PINJAM POLA SYARIAH AUSATH BANYUWANGI) - Muhammad Syarofi (Islamic Banking Department, Faculty of Islamic Economics and Business, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, Indonesia., 2022)
Islamic non-bank financial institutions, namely islamic cooperatives USPPS Ausath as financial institutions that are also not separated from the risk and return, with the risk or risk forces the cooperative to identify and recognize every risk that is happening and that will be faced in the hope of being able to minimize the risk that occurs so as to be able to get optimal return. This research study is obtained through a qualitative approach, using data in the form of written or oral sentences from a selected source, through events or knowledge of study projects that are descriptive, this type of research uses case study methods. Risk management carried out by the sharia cooperative USPPS Ausath implements risk management effectively and competitively by the individual sharia cooperative USPPS Ausath and the sharia cooperative business unit USPPS Ausath, through consolidation with subsidiaries under the auspices of sharia cooperatives USPPS Ausath and still supervised by the Commissariat Board of sharia cooperatives USPPS Ausath, and the Sharia Supervisory Board.